2013
DOI: 10.1590/s1413-35552012005000129
|View full text |Cite
|
Sign up to set email alerts
|

Identification and agreement of first turn point by mathematical analysis applied to heart rate, carbon dioxide output and electromyography

Abstract: BackgroundThe second heart rate (HR) turn point has been extensively studied, however there are few studies determining the first HR turn point. Also, the use of mathematical and statistical models for determining changes in dynamic characteristics of physiological variables during an incremental cardiopulmonary test has been suggested. ObjectivesTo determine the first turn point by analysis of HR, surface electromyography (sEMG), and carbon dioxide output () using two mathematical models and to compare the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“…VAT was determined from the loss of parallelism between oxygen uptake (VO 2 ) and carbon dioxide production (VCO 2 ) by three properly trained observers, as previously described by Zamunér et al ( 20 ) and Higa et al ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…VAT was determined from the loss of parallelism between oxygen uptake (VO 2 ) and carbon dioxide production (VCO 2 ) by three properly trained observers, as previously described by Zamunér et al ( 20 ) and Higa et al ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The VAT was determined from a loss of parallelism between VO 2 (oxygen consumption) and VCO 2 (carbon dioxide output) by three properly trained observers, as previously described by Zamunér et al 16 and Higa et al 17 .…”
Section: Methodsmentioning
confidence: 99%
“…The reason for the investigation of alternative methods is the intention to apply models that can be used in physical training and rehabilitation environments. The application of mathematical models in more accessible variables is a low-cost alternative and can produce reliable results [3,9,25,27]. Conventional protocols are designed to adequately determine AT in athletes and healthy individuals.…”
mentioning
confidence: 99%
“…We concluded that the mathematical model was suitable for detecting the AT in both healthy and myocardial infarction subjects. that the mathematical models were sensitive in the detection of AT, these studies were performed in the vast majority with healthy individuals [3,9,25,27], and to our knowledge, there have not been any studies to date that have applied mathematical models to determine the AT in cardiac patients. We hypothesized that individuals with previous myocardial infarction (MI) have a breaking point in the cardiopulmonary and muscle variables during the exercise protocol and that this point corresponds to the AT, similar to healthy individuals.…”
mentioning
confidence: 99%